Fluoridation of water and cancer mortality in the U.S.A. - Doll, R; Kinlen, L (1977)
Authoritative statements that fluoridation of public water supplies is not associated with any increase in cancer have been challenged on the basis of data which, it is claimed, show that cancer mortality in the United States rose more sharply in cities with fluoridated water than in those without. However, during the period of study (1950-70) the population structures of these cities changed substantially. When account is taken of age, sex, and ethnic group the ratio between observed cancer mortality and expected cancer mortality fell slightly in the cities with fluoridated water and did not change in the non-fluoridated cities.